Keeping our heads above water: Spatially heterogeneous social vulnerabilities and climate adaptation - Stefano Ceolotto; Niall Farrell (The Economic and Social Research Institute (ESRI), 2024)
Climate change is among the biggest challenges of our time. Climate impacts and socioeconomic vulnerability are spatially heterogeneous. Hence, adaptation policies are more effective when designed at lower administrative levels. However, spatially-detailed social vulnerability profiles are often not available. This paper employs a Conditional Monte Carlo simulation-based methodology to generate social vulnerability profiles representative at the electoral division level. These are used to investigate climate risk, considering flood risk in Ireland as a case study. The results highlight that while population exposure offers insight into flood risk patterns, incorporating socioeconomic vulnerability allows a more precise identification of areas of priority.
Keywords: C63; Q54; R11; Y91; 330; Flood risk; Socioeconomic vulnerability; Small area estimation; Electoral divisions; Climate change; Ireland